Conditionality in Chinese bilateral lending - Mikael Mattlin; Matti Nojonen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
China.s long insistence on non-interference and sovereignty and frequent criticism of Western in-terventionism has contributed to a widely held impression that China lends and invests abroad without attaching policy conditions. This discussion paper surveys the general policy debate on conditionality in lending, as well as China.s own debate on conditionality. We then examine bila-teral loans provided by Chinese state-owned policy banks, notably China Exim Bank, arguing that the assumption of China.s shunning conditionality is valid only if the term is taken narrowly to imply the specific set of policy conditions (e.g. privatisation and financial liberalisation) routinely called for by World Bank Group lenders. Based on a literature review and analysis of loan features along with tentative evidence from empirical cases of Chinese bilateral lending, we identify four hypothetical types of conditionality: political conditionality, embedded conditionality, cross-conditionality and emergent conditionality. In all likelihood the last three types of conditionality are not imposed by a unitary state actor, but emerge as an indirect consequence of the voluminous busi-ness activities of Chinese state-linked lenders and enterprises in developing countries.
URN:NBN:fi:bof-201408071951
Keywords: F34; F36; F59; 330; China; bilateral lending; conditionality; policy banks